Upskilling and Reskilling: Adaptive Strategies For HR Management in Facing The Industrial Revolution 5.0 - Fauziah F Farawowan (PT. Hafasy Dwi Nawasena, 2025)
The Industrial Revolution 5.0 has given rise to a new paradigm in human resource (HRM) management, emphasizing the integration of technological advancements and humanistic values. This shift demands a shift in the role of HR from an administrative function to a strategic partner for organizations capable of bridging the collaboration between humans and machines. In this context, upskilling and reskilling strategies are crucial instruments for addressing the challenges of technological disruption and competency gaps. By enhancing technical skills and soft skills such as empathy and critical thinking, the workforce is expected to be more adaptive to future industrial dynamics. This research uses a qualitative method with a literature review approach to explore practices and theories related to HRM development strategies in the Industrial Revolution 5.0 era. Analysis is conducted using a thematic approach to identify organizational policy patterns in responding to structural changes. The study results indicate that the success of upskilling and reskilling programs is largely determined by an inclusive learning culture, transformational leadership, and digital infrastructure readiness. Integrating training strategies within the Strategic Human Resource Management (SHRM) framework is key to sustainability. Therefore, HRM development strategies should not be merely reactive but should be a long-term investment for organizational competitiveness and sustainability.